2021
DOI: 10.1002/csc2.20465
|View full text |Cite
|
Sign up to set email alerts
|

Differential survival of alfalfa varieties interseeded into corn silage

Abstract: Interseeding alfalfa (Medicago sativa L.) into silage corn (Zea mays L.) can improve forage yield, farm profitability, and soil conservation, but unreliable alfalfa establishment hampers on‐farm adoption. This study evaluated seedling survival and growth of 36 alfalfa varieties differing in reported plant traits when interseeded at two Wisconsin sites in 2015 and at single sites in Wisconsin, Michigan, and Pennsylvania in 2016. Subplots of alfalfa varieties were sprayed with prohexadione‐calcium (PHD) at 0 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 39 publications
3
26
2
Order By: Relevance
“…In the seeding year, establishment of alfalfa under the corn was poor in Rosemount 2017 for both treated and untreated alfalfa. This is in contrast to observations of Grabber [13] and Grabber et al [16] who reported a significant increase of alfalfa stem density when PHX was applied to intercropped alfalfa in Wisconsin. However, as in this study, Grabber et al [16] indicated that there was no significant response to PHX on alfalfa stem density in the studies conducted in Michigan and Pennsylvania.…”
Section: Alfalfa Stem and Plant Densitycontrasting
confidence: 99%
See 4 more Smart Citations
“…In the seeding year, establishment of alfalfa under the corn was poor in Rosemount 2017 for both treated and untreated alfalfa. This is in contrast to observations of Grabber [13] and Grabber et al [16] who reported a significant increase of alfalfa stem density when PHX was applied to intercropped alfalfa in Wisconsin. However, as in this study, Grabber et al [16] indicated that there was no significant response to PHX on alfalfa stem density in the studies conducted in Michigan and Pennsylvania.…”
Section: Alfalfa Stem and Plant Densitycontrasting
confidence: 99%
“…This is in contrast to observations of Grabber [13] and Grabber et al [16] who reported a significant increase of alfalfa stem density when PHX was applied to intercropped alfalfa in Wisconsin. However, as in this study, Grabber et al [16] indicated that there was no significant response to PHX on alfalfa stem density in the studies conducted in Michigan and Pennsylvania. Grabber et al [16] also reported differences in shade tolerance among alfalfa cultivars, but the cultivars used in this study were not included in the Grabber et al [16] study.…”
Section: Alfalfa Stem and Plant Densitycontrasting
confidence: 99%
See 3 more Smart Citations